Cystic fibrosis: a model system for precision medicine. Issue 3 (June 2016) - Martiniano, Stacey L.; Sagel, Scott D.; Zemanick, Edith T.
Abstract : Purpose of review: Development of cystic fibrosis transmembrane conductance regulator (CFTR) modulators, small molecule therapies that target the basic defect in cystic fibrosis (CF), represents a new era in CF treatment. This review highlights recent progress in CF therapeutics as an example of precision medicine and personalized approaches to test CFTR modulators using preclinical model systems. Recent findings: CFTR modulators are now clinically available for approximately 50% of the United States CF population. The CFTR potentiator, ivacaftor, is approved for people with CF ages 2 years and older with at least one gating mutation (G551D, G1244E, G1349D, G178R, G551S, S1251N, S1255P, S549N, or S549R) or the R117H conductance mutation. The recent Food and Drug Administration approval of the corrector/potentiator combination, lumacaftor/ivacaftor, expands modulator therapy to people with CF homozygous for the F508del mutation, ages 12 years and older. Ivacaftor and lumacaftor, however, do not fully restore CFTR activity. Thus, next-generation correctors and potentiators are in development. Read-through agents targeting nonsense mutations and genotype agnostic treatments (gene-editing and gene therapy) are also in various phases of clinical development. Summary: CFTR modulators promise to transform the therapeutic landscape in CF in a precision based fashion. Areas of ongoing research include developing drugs for all mutation classes so that all persons with CF can benefit from these therapies, and refining preclinical assays that allow the selection of the most effective treatments on an individual basis.